(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
This study aimed to investigate the effect of frozen live food (Daphnia magna) and artificial diets on growth performance, feed conversion ratio and survival of Cyprinus carpio fry reared in 25-liter glass aquaria. Duplicate groups of fry were fed on the tested diets three times a day to satiation for 21 days. The results revealed that the growth rates (weight gain, % weight gain) were significantly (P<0.05) affected by the used diets. Fry fed on the frozen live food showed the worst growth rates, even their feed conversion ratio expressed the lowest value compared with the results obtained from fry fed on the artificial diets, although survival was not significantly (P>0.05) affected with the different diets. No significant differences (P>0.05) were noticed in the results obtained from fry fed on the different artificial diets. تم إجراء البحث لدراسة مدى تأثير كل من العلف الطبيعي المجمد ، و نوعين من العلائق الاصطناعية على النمو، معامل التحويل الغذائي و البقاء على قيد الحياة لصغار سمك الكارب العادي (Cyprinus carpio) ، الذي تم تربيته في أحواض زجاجية سعة 25 ليتر من المياه العذبة. علفت الصغار (بمعدل مكررين لكل معاملة) ثلاث مرات في اليوم حتى الشبع ، لمدة 21 يوماً . أوضحت النتائج أن مظاهر النمو المختلفة تأثرت على نحوٍ واضح(P<0.05) بالأعلاف المستخدمة. حققت الصغار التي تغذت على العلف الطبيعي المجمد أدنى معدلا ت للنمو ( معدل الكسب بالوزن والنسبة المئوية للوزن المكتسب) ، و كذلك الأمر مع معامل التحويل الغذائي لهذه الصغار ، إذ سجل قيماً منخفضة مقارنة بمثيلاتها التي قدم لها الأعلاف الاصطناعية, مع العلم أن البقاء على قيد الحياة لم يتأثر(P>0.05) . كذلك لم تسجل اختلافات جوهرية (P>0.05) بين نوعي العلف الاصطناعي المستخدم.